Kerjasama Internasional Korea Selatan Dengan Indonesia (Studi Kasus Peningkatan Status Kerjasama Dari Strategic Partnership Menjadi Special Strategic Partnership Tahun 2017) - Ervina Arini; Anna Yulia Hartati (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2021)
This research analyzes the bilateral cooperation relationship between Indonesia and South Korea regarding the increase in the status of cooperation from Strategic Partnership to Special Strategic Partnership. In this case, the focus of research is on the factors that made Indonesia agree to increase the status of cooperation to become a Special Strategic Partnership with South Korea. In addition to the existence of a free and active policy which is the basis of Indonesia's foreign policy, which makes Indonesia free to make friends and establish cooperation with any country, there is also a foreign policy. During the reign of President Joko Widodo, that accelerated infrastructure development, which of course required investment from other countries, and South Korea became one of the countries that invested in Indonesia. By conducting qualitative research, namely by reviewing the literature, and by using the concept of international cooperation, this thesis finds the factors that made Indonesia agree to increase the status of cooperation with South Korea to become a Special Strategic Partnership, namely, economic factors, defense and security factors, and social culture factors.